Anatomical and Surgical Evaluation of the Common Marmoset as an Animal Model in Hearing Research - Kurihara, Sho; Fujioka, Masato; Hata, Junichi; Yoshida, Tomohiko; Hirabayashi, Motoki; Yamamoto, Yutaka; Ogawa, Kaoru; Kojima, Hiromi; Okano, Hirotaka James (Frontiers in Neuroanatomy, 2019)
Recent studies have indicated that direct administration of viral vectors or small compounds to the inner ear may aid in the treatment of Sensorineural hearing loss (SNHL). However, due to species differences between humans and rodents, translating experimental results into clinical applications remains challenging. The common marmoset (Callithrix jacchus), a New World monkey, is considered a pre-clinical animal model. In the present study, we describe morphometric data acquired from the temporal bone of the common marmoset in order to define the routes of topical drug administration to the inner ear. Dissection and diffusion tensor tractography (DTT) were performed on the fixed cadaverous heads of 13 common marmosets. To investigate potential routes for drug administration to the inner ear, we explored the anatomy of the round window, oval window (OW), semicircular canal, and endolymphatic sac (ES). Among these, the approach via the round window with posterior tympanotomy appeared feasible for delivering drugs to the inner ear without manipulating the tympanic membrane, minimizing the chances of conductive hearing loss. The courses of four critical nerves [including the facial nerve (FN)] were visualized using three-dimensional (3D) DTT, which may help to avoid nerve damage during surgery. Finally, to investigate the feasibility of actual drug administration, we measured the volume of the round window niche (RWN), which was approximately 0.9 μL. The present findings may help to establish experimental standards for evaluating new therapies in this primate model.